2020
DOI: 10.1002/ece3.6351
|View full text |Cite
|
Sign up to set email alerts
|

Dark diversity reveals importance of biotic resources and competition for plant diversity across habitats

Abstract: Species richness is the most commonly used metric to quantify biodiversity. However, examining dark diversity, the group of missing species which can potentially inhabit a site, can provide a more thorough understanding of the processes influencing observed biodiversity and help evaluate the restoration potential of local habitats. So far, dark diversity has mainly been studied for specific habitats or large‐scale landscapes, while less attention has been given to variation across broad environmental gradients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
2
13
0
1
Order By: Relevance
“…Our study showed that plant dark diversity was generally higher in sites with relatively tall vegetation andin the open dry habitats -also in sites with higher soil nitrogen content and where the vegetation is homogenous. This is supported by recent studies, showing that plants preferring higher nutrient availability is also less often part of the dark diversity (Moeslund et al 2017) and that plant dark diversity is generally higher in relatively nutrient rich sites (Fløjgaard et al 2020). In nature, overgrowth by tall herbs is a severe threat to low-statured slowly growing plants as these are outcompeted through asymmetric competition (Freckleton and Watkinson 2001;Hautier et al 2018;Lepš 1999).…”
Section: Discussionmentioning
confidence: 70%
“…Our study showed that plant dark diversity was generally higher in sites with relatively tall vegetation andin the open dry habitats -also in sites with higher soil nitrogen content and where the vegetation is homogenous. This is supported by recent studies, showing that plants preferring higher nutrient availability is also less often part of the dark diversity (Moeslund et al 2017) and that plant dark diversity is generally higher in relatively nutrient rich sites (Fløjgaard et al 2020). In nature, overgrowth by tall herbs is a severe threat to low-statured slowly growing plants as these are outcompeted through asymmetric competition (Freckleton and Watkinson 2001;Hautier et al 2018;Lepš 1999).…”
Section: Discussionmentioning
confidence: 70%
“…This was generally supported by both linear modelling and the GDM despite the profoundly different analytical approaches of these methods. Environmental effects on dark diversity size were previously found for plants (local dark diversity size correlated positively with soil fertility and pH and negatively with soil organic carbon; Fløjgaard et al, 2020) and fleas (Krasnov et al, 2022). In the latter study, the dark diversity size of fleas was considered (a) for flea communities on a single host species (= component communities; Poulin, 2007) rather than on all host species in a locality (= compound communities;Poulin, 2007) and (b) at a much larger geographic scale…”
Section: Environmental Effects On Missing Species and Linksmentioning
confidence: 78%
“…Species absent from a locality either can theoretically inhabit it or not. In the former case, they belong to a so-called regional 'habitat-specific species pool' defined as a set of species occurring in a surrounding region and assembled via largescale evolutionary and/or biogeographic processes so that these species can inhabit a given locality because its ecological conditions are suitable for them (Cornell & Harrison, 2014;Fløjgaard et al, 2020;Pärtel et al, 1996Pärtel et al, , 2011Zobel, 2016). A local set of species represents a subset of the species pool assembled via local processes, such as interspecific interactions or dispersal limitations (Cornell & Harrison, 2014;Pärtel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Zeng Xianlai researched the sustainability of critical metals and e-waste management (Zeng et al 2015 ; 2018 ). Also, other scholars have carried out analyses from the aspects of biological resources diversity (Fløjgaard et al 2020 ), medical and health resources (Takura et al 2021 ), sustainable circulation of water resources (Xiang et al 2021 ; Shen et al 2014 ; Sutapa et al 2021 ), and mineral resource safety (Baninla et al 2019 ; Shao 2019 ; Zhang et al 2021 ). Based on the research of scholars, this paper systematically sorts out the research in the field of resource security and provides suggestions for policy.…”
Section: Introductionmentioning
confidence: 99%